Bioethics in Medicine and Society - Heston, Thomas F.; Ray, Sujoy (IntechOpen, 2021)
Bioethics is the application of ethics to the broad field of medicine, including the ethics of patient care, research, and public health. In this book, prominent authors from around the globe discuss the complexities of bioethics as they apply to our current world. Topics range from the philosophical bioethics of the evolution of thinking about marriage from a religious standpoint to the bioethics of radiation protection to value-based medicine and cancer screening for breast cancer. Bioethics in Medicine and Society is wide-ranging, with additional chapters on the ethics of geoengineering, complementary and alternative medicine, and end-of-life ethical dilemmas. Readers with find that the field of bioethics has broad implications throughout society from our most intimate interpersonal relationships to policies being implemented on a global scale.